Critical key points for anesthesia in experimental research involving sheep (Ovis aries) - Ruxandra Costea; Tiberiu Iancu; Alexandru Duțulescu; Cătălin Nicolae; Florin Leau; Ruxandra Pavel (Open Veterinary Journal)
Anesthesia and analgesia have a major impact on ensuring animal welfare and safety, resulting in reduced stress response and effective pain control, ensuring the comfort of the animal, promoting faster recovery, and reducing the risk of complications associated with various research procedures. Each stage of anesthesia in sheep is vital for maintaining the animal's welfare, ensuring procedural success, minimizing stress, risks, and complications, and optimizing the quality of research data. Proper attention to detail and adherence to best practices at each stage contribute to the overall success of anesthesia management in sheep. Anesthesia protocols should suit individual requirements for each sheep, in light of factors such as health status, procedure duration, and desired anesthesia depth. Meticulous monitoring, adherence to best practices, and prompt intervention are essential for minimizing the risks of complications during sheep anesthesia and ensuring the safety and welfare of the animals undergoing anesthesia for research purposes. This article presents the main key points that can improve anesthetic management for sheep involved in experimental research to minimize stress response and complications, enhancing animal safety, welfare, and comfort during and after procedures. Multimodal anesthesia approaches ensure effective pain relief, tailored to the specific needs of individual animals or procedures, optimizing outcomes and minimizing risks. Anesthesia management contributes to improved research data collection under conditions that enhance the validity and reliability of results. Sheep's impressive capacity to maintain homeostasis even during extended periods of anesthesia highlights the critical importance of upholding data quality in alignment with the universally accepted principles of Replacement, Reduction, and Refinement for ethical animal research. By adhering to these principles, researchers can minimize the number of animals used, reduce any potential discomfort or distress experienced by the animals, and refine procedures to optimize animal welfare while still achieving scientific objectives. [Open Vet J 2024; 14(9.000): 2129-2137]